A pesquisa qualitativa em ciências humanas e sociais: evolução e desafios - Antonio Chizzotti (Universidade do Minho, 2003)
This paper analyses the evolution of qualitative research, divides her evolution in different phases in the past century, and points out the present challenges that has qualitative research. The encompassment that the word qualitative asserts in research, suggests the increasing complexity of questions that has informed such researchs. The evolution since some expressive landmarks shows different conceptions and contributions that have changed the qualitative researchs and an extensive mouvement of ideas, practices, and technics of research in human sciences in opposition to a sole model.